The Influence of ShopeePay and Shopee PayLater Features to Public Shopping Interest of the Bangka Belitung Islands Province on the Shopee Application - Charisma Riskidilpha; David Stanley; Faradeska Amalia; Rulyanti Susi Wardhani (Nusantara Science and Technology Proceedings, 2022)
This study aims to analyze the effect of the ShopeePay and Shopee PayLater features on the shopping interest of the people of the Bangka Belitung Islands Province on the Shopee application. The formulation of the problem in this study is whether the ShopeePay and Shopee PayLater features affect the shopping interest of the people in the Province of the Bangka Belitung Islands. The respondents used in this study are people in the Bangka Belitung Islands Province who use the Shopee application with the ShopeePay and Shopee PayLater features. The sample used in this study was 400 people divided into several districts and cities in the Province of the Bangka Belitung Islands. The distribution of the questionnaire was carried out directly by interviewing and using Google Forms to respondents who used the Shopee application. The type of research used in this research is quantitative research with an accidental sampling technique. The data analysis technique used in this study was multiple linear regression which was tested to test data quality, classical assumptions, and hypothesis testing. The results of the study illustrate that the ShopeePay and Shopee PayLater features affect the shopping interest of the people in the Province of the Bangka Belitung Islands on the Shopee application. The ShopeePay feature has a dominant influence on the ease of payment so it has a positive effect on people's shopping interest because Shopee PayLater provides solutions for payments with a later payment system to increase people's shopping interest.